Association of sociocultural factors with initiation of the kidney transplant evaluation process. Issue 1 (14th August 2019) - Hamoda, Reem E.; McPherson, Laura J.; Lipford, Kristie; Jacob Arriola, Kimberly; Plantinga, Laura; Gander, Jennifer C.; Hartmann, Erica; Mulloy, Laura; Zayas, Carlos F.; Lee, Kyung Na; Pastan, Stephen O.; Patzer, Rachel E.
Abstract : Although research shows that minorities exhibit higher levels of medical mistrust, perceived racism, and discrimination in healthcare settings, the degree to which these underlying sociocultural factors preclude end‐stage renal disease (ESRD) patients from initiating kidney transplant evaluation is unknown. We telephone surveyed 528 adult ESRD patients of black or white race referred for evaluation to a Georgia transplant center (N = 3) in 2014‐2016. We used multivariable logistic regression to examine associations between sociocultural factors and evaluation initiation, adjusting for demographic, clinical, and socioeconomic characteristics. Despite blacks (n = 407) reporting higher levels of medical mistrust (40.0% vs 26.4%, P < .01), perceived racism (55.5% vs 18.2%, P < .01), and experienced discrimination (29.0% vs 15.7%, P < .01) than whites (n = 121), blacks were only slightly less likely than whites to initiate evaluation (49.6% vs 57.9%, P = .11). However, after adjustment, medical mistrust (odds ratio [OR]: 0.59; 95% confidence interval [CI]: 0.39, 0.91), experienced discrimination (OR: 0.62, 95% CI: 0.41, 0.95), and perceived racism (OR: 0.61; 95% CI: 0.40, 0.92) were associated with lower evaluation initiation. Results suggest that sociocultural disparities exist in early kidney transplant access and occur despite the absence of a significant racial disparity in evaluation initiation. Interventions to reduce disparities in transplantation access should target underlying sociocultural factors, not just race. Abstract : A telephone survey administered to adult end‐stage renal disease patients referred for kidney transplant evaluation showed that those who exhibited high levels of distrust of healthcare organizations, experienced discrimination in healthcare, or perceived racism in healthcare settings were less likely to initiate the transplant evaluation process at a transplant center.